2012
DOI: 10.1093/eurheartj/ehr482
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pycnogenol on endothelial function in patients with stable coronary artery disease: a double-blind, randomized, placebo-controlled, cross-over study

Abstract: This study provides the first evidence that the antioxidant Pycnogenol improves endothelial function in patients with CAD by reducing oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(132 citation statements)
references
References 45 publications
4
122
0
2
Order By: Relevance
“…PYC can noticeably reduce many of the risk factors associated with cardiovascular disease (CVD), such as systolic blood pressure, glycosylated hemoglobin, hyperlipidemia, and platelet aggregation (Parveen et al, 2009). PYC also improves endothelial function in patients with coronary artery disease by reducing oxidative stress (Enseleit et al, 2012). Enzogenol has been shown to block early atherogenesis and may therefore be useful for treating atherosclerosis (Kim et al, 2010).…”
Section: Organ Protective Effects Of Pbe Cardiovascular Protectionmentioning
confidence: 99%
“…PYC can noticeably reduce many of the risk factors associated with cardiovascular disease (CVD), such as systolic blood pressure, glycosylated hemoglobin, hyperlipidemia, and platelet aggregation (Parveen et al, 2009). PYC also improves endothelial function in patients with coronary artery disease by reducing oxidative stress (Enseleit et al, 2012). Enzogenol has been shown to block early atherogenesis and may therefore be useful for treating atherosclerosis (Kim et al, 2010).…”
Section: Organ Protective Effects Of Pbe Cardiovascular Protectionmentioning
confidence: 99%
“…et al investigated the big ET-1 levels in a young population and found that the plasma big ET-1 levels were significantly higher in the patients with CAD than that without 27) . Several other studies have focused on the impact of currently available medications on the endothelial function in patients with stable CAD using the ET-1 level as a marker, but most of these studies included a small sample size, and no data are currently available regarding the relationship between ET-1 and the severity of CAD [28][29][30] . In addition, The plasma ET-1, who has a short half-life, does not reflect the true ET-1 value.…”
Section: Auc=064mentioning
confidence: 99%
“…All the ABPM measurements were performed using a validated device (Tracker NIBP2, Delmar, Del Mar Reynolds Medical, Hertford, UK). [30] In these previous studies approved by our institutional ethical committee all patients have granted their informed consent [28,29]. For this retrospective analysis pseudonymised data of these two previous pharmaceutical studies were used.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies [28,29] we used ABPM to assess changes in blood pressure with drugs or food additives with uncertain effects on blood pressure. Here we used these datasets to study the reproducibility of ABPM.…”
Section: Original Articlementioning
confidence: 99%